PEMANFAATAN CENDAWAN MIKORIZA ARBUSKULAR (CMA) UNTUK PERTUMBUHAN DAN PERKEMBANGAN BIBIT KELAPA SAWIT (Elaeis gueneensis jacq.) DI PEMBIBITAN AWAL - Jaka Fitra Perdana; Murniati '; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Palm oil (Elaeis guineensis Jacq) is a commodity that produces vegetable oils are important in beside coconut, nuts and corn. Palm oil plantations in Riau province ranks first in comparison to other plantations such as palm, rubber and cocoa. According to the Stastik Central Bureau in 2011 vast palm oil plantations of Riau reached 2,256,538 ha. Most of the plant is less productive because of age and need rejuvenation. Nurseries is one aspect of agronomy that was instrumental in the early stages of crop management to be cultivated. Planting medium used in palm oil nurseries is topsoil with a thickness of 10-20 cm from the ground. Alternative medium that can be used is marginal soils such as sand. Sand can be used for the planting medium with the addition of organic fertilizer and Arbuskular Mycorrhizal Fungi (AMF). Mycorrhizae is a form of mutualitik symbiotic relationship between fungi with plant roots, fungi or plants both equally benefit from this association. The research with experiment by methods completely randomized design (CRD) consisting of 3 treatments. Each treatment was repeated 6 times to obtain 18 experimental units, each unit comprising 2 plant experiments. There treatment is giving of AMF : C0 = Giving AMF with a dose of 0 g/polybag, C1 = Giving AMF with a dose of 10 g/polybag, C2 = Giving AMF with a dose of 20 g/polybag. The results of this study showed that giving of Arbuskular Mycorrhizae Fungi in planting medium is not a real effect on seedling height, leaf length, number of leaves, fresh weight, ratio of dry weight of roots and canopy of palm seedlings. The best treatment was obtained by administration of AMF 10 g/polybags in the nursery medium.   Keywords: Pre Nurseries, Arbuskular Mycorrhizae Fungi (AMF), Palm Oil Seed, Growth and Development.